Knowledge Study of the Oral Cavity and Systemic Diseases of Dentistry and Medical Students - Siregar, Darmayanti; Marbun, Astri Hartati; Refwita, Nindy Nafisah; Khairima, Nisa; Jannah, MiftahKhul (Dentistry Faculty, 2023)
Background: Oral health is a healthy condition of hard and soft tissue and related components of the oral cavity, allowing each individual to eat, speak and interact socially. An unhealthy oral cavity can cause several diseases affecting general health and quality of life. Caries, periodontal disease, and xerostomia are oral cavity diseases that often occur. It can disrupt the normal flora, causing infection to suppress the immune system that can worsen other systemic diseases. Students' awareness of the importance of oral health aims to make an early diagnosis so that practitioners can carry out adequate treatment to prevent disease. Objective: The evaluation of knowledge about oral cavity and systemic diseases in dentistry and medicine students, University of North Sumatra, Indonesia Materials and Methods: The study was conducted with 140 dentists and medical students. This research used an analytic survey with a cross-sectional design using a questionnaire. Sampling using a simple random sampling method and analyzed by Chi-square test. Results: The level of knowledge of dental students with good knowledge was 94.29%, sufficient knowledge was 5.71%, and no knowledge was lacking. For medical students, 77.14% had good knowledge, 18.57% had adequate knowledge, and 4.29% lacked knowledge. Conclusion: The level of knowledge about oral cavity diseases with systemic diseases in college students is suitable, although some respondents have sufficient to insufficient knowledge.